(untitled) (Sociologisk Forskning, 1995)
The biologiscal continuation of self In this article I argue that although individual changes or ”biographies” are crucial for the dynamics and functioning of modem societies, sociological theorizing has tended to downplay the importance of the biographical constitution of self. Methodologically sociologists have relied too much upon explanatory ” types” rather then starting from the social fact of ”variation”, the chaotic nature of the actual functioning of society has been ignored and the subjective element in societal changes has been defined out of existence. A model for analyzing the biographical constitution of self is suggested including such aspects as risk management and strategic thinking, biographical reflexivity, biographical work, repair work, biographical convertability, biographical events and normal biographies. The arguments rely heavily upon recent biography research in Germany and are illustrated by reference to the founder of the Zionist movement, Theodor Herzl, modern art and literature and studies on the biographical adaption of former GDR citizens in the process of German unification.